Stress Management Due to Work Fatigue in Farmers: Manajemen Stress Akibat Kelelahan Kerja Pada Petani (AgroNurse Kesehatan : Jurnal Pengabdian Masyarakat, 2023)
Working as a farmer has various risk factors, one of which is experiencing work stress. High workload causes work stress on farmers. Farmers who experience work stress will have an impact on decreasing health conditions. So, it is important to know psychological health as a support for welfare and increased productivity. This community service activity aims to provide health education about stress management due to work fatigue to farmers in agricultural areas. The target of this activity is approximately 30 farmers in Sukoreno Village, Kalisat District, Jember Regency. Activities began with basic health checks such as measuring blood pressure and blood sugar, then continued with health education and the practice of stress management techniques with deep breathing relaxation and progressive muscle relaxation. The result of this activity is an increase in public knowledge about work stress and how to overcome it, as well as an increase in farmers' skills in managing stress with deep breathing relaxation techniques and progressive muscle relaxation. Socialization of stress management due to work fatigue needs to be increased with a broader target such as fishermen, factory workers, and other communities in agro-industrial areas.